On the Solutions of the Coupled Nonlinear Parabolic Equations (Journal of Partial Differential Equations, 1996)
By means of the fixed point technique and integral estimation method, we study the solutions of periodic boundary value problem and initial value problem for the coupled nonlinear parabolic equations. The global classical solutions of the mentioned problems are shown to exists.
Keywords: Nonlinear parabolic equation; existence and uniqueness global solution